The Role of School Principal as Motivator in Utilization of Digital Technology at SMAN 5 Takengon - Basidin Mizal; Julianita Julianita; Tathahira Tathahira (Universitas Teuku Umar, 2023)
This study attempts to describe the untold experience of digital technology utilization for learning at one of high schools located in the most central district in Aceh province. This study aimed to reveal the strategies and challenges implemented and experienced by the school principal and teachers at SMAN 5 Takengon, Central Aceh regency, Aceh province. This qualitative study involved three respondents namely a school principal, a regular teacher and a teaching staff. In collecting the data, the researcher employed an observation and interview session. The findings revealed that as a motivator, the principal at SMAN 5 Takengon implemented several strategies to positively encourage teachers to utilize the digital technology in the classroom through creating a positive working atmosphere, encouraging the teachers individually, providing the rewards, supporting the teachers with learning resources. However, the obstacles such as teachers’ unproductive age and unfamiliarity, and consistent commitment became two most challenging factors in guaranteeing the utilization of digital technology for learning at SMAN 5 Takengon.